Does Public Financial News Resolve Asymmetric Information? - Tetlock, Paul C. (Review of Financial Studies, 2010)
I use uniquely comprehensive data on financial news events to test four predictions from an asymmetric information model of a firm's stock price. Certain investors trade on information before it becomes public; then, public news levels the playing field for other investors, increasing their willingness to accommodate a persistent liquidity shock. Empirically, I measure public information using firms' stock returns on news days in the Dow Jones archive. I find four patterns in postnews returns and trading volume that are consistent with the asymmetric information model's predictions. Some evidence is, moreover, inconsistent with alternative theories in which traders interpret news differently for rational or behavioral reasons.